2015
DOI: 10.3233/jad-150428
|View full text |Cite
|
Sign up to set email alerts
|

Age and Its Association with Low Insulin and High Amyloid-β Peptides in Blood

Abstract: Age is the major risk factor for developing Alzheimer’s disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ40. Apolipoprotein E4 allele (ApoE4) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Previous studies provide evidence on the link between ASCVD as assessed by CVRF prevalence and age-related dementia (11). To that end, converging data demonstrate that circulating Aβ1-40 levels are associated with CVRF burden, vascular ageing and atherosclerosis (14,16,(34)(35)(36)(37). In agreement with these findings, we observed that a high CVRF burden as well as high estimated ASCVD risk, are associated with increased BACE1-AS expression levels.…”
Section: ) Discussionsupporting
confidence: 89%
“…Previous studies provide evidence on the link between ASCVD as assessed by CVRF prevalence and age-related dementia (11). To that end, converging data demonstrate that circulating Aβ1-40 levels are associated with CVRF burden, vascular ageing and atherosclerosis (14,16,(34)(35)(36)(37). In agreement with these findings, we observed that a high CVRF burden as well as high estimated ASCVD risk, are associated with increased BACE1-AS expression levels.…”
Section: ) Discussionsupporting
confidence: 89%
“…While the included studies showed no association between age and plasma amyloid levels, results by a study by Schupf et al () showed that plasma Aβ 42 increased with age in a DS population. In sporadic AD, in contrast, age was found to be more consistently associated with increased levels of plasma Aβ peptides (Fukumoto et al, ; Gabelle et al, ; Hanon et al, ; Li et al, ), and only a few articles reported no significant correlation (Lövheim et al, ; Mehta, Pirttilab, Patricka, Barshatzkya, & Mehta, ). These discrepancies may be due to a non‐linear relationship between age and Aβ levels in individuals with AD, with levels increasing prior to dementia diagnosis, but decreasing again during later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular dysfunction, as one of the most common pathological changes in Alzheimer's disease and a mechanism of vascular aging, can be caused when amyloid beta (Aβ) deposits in cerebral blood vessels [ 49 ]. The concentration of Aβ in the brain cells of rats increased with age in animal research [ 50 ], while in clinical studies, the circulating levels of Aβ40 in the elderly were higher than those in the young even in the absence of diabetes, stroke and other diseases [ 51 ]. Additionally, elevated circulating levels of amyloid β40 can also be found in patients with coronary heart disease [ 52 ].…”
Section: The Mechanism Of Vascular Agingmentioning
confidence: 99%